Zredukuj wyrazy podobne:
a) 3x²-5x+2+2x-4+x²=
b) -4x²-3+3x-x²-4x+5=
c) x³-4x²+5x-1-3x³+4x²-7x+4=
d) 2+3x-x²-2x³+5x³-4x²-3x+5=
e) 9x²-3x+1-6x²-5x-3-6+2x-x²=
f) 4-2x-3x²-5x²+2x-3-5+x+4x²=
g) -2x³-8x-4+2x²-6+2x-x³-3x-4x²+6x-1=
h) 8-7x-x³+4x²-6x-5x²-2+10x-4x³-2x=

3

Odpowiedzi

2010-02-04T20:22:47+01:00
A) 3x²-5x+2+2x-4+x²=4xkwadrat-3x-2
b) -4x²-3+3x-x²-4x+5=-5xkwadrat+2-x
c) x³-4x²+5x-1-3x³+4x²-7x+4=-2xszscian-2x+3
d) 2+3x-x²-2x³+5x³-4x²-3x+5=7-5xkwadrat+3xszescian
e) 9x²-3x+1-6x²-5x-3-6+2x-x²=2xkwadrat-6x-8
f) 4-2x-3x²-5x²+2x-3-5+x+4x²=-4+x-4xkwadrat
g) -2x³-8x-4+2x²-6+2x-x³-3x-4x²+6x-1=-3xszescian+3x-11-2xkwadrat
h) 8-7x-x³+4x²-6x-5x²-2+10x-4x³-2x=6+x-5xszescian-xkwadrat
Najlepsza Odpowiedź!
2010-02-04T20:23:41+01:00
A) 3x²-5x+2+2x-4+x²= 4x²-3x-2
b) -4x²-3+3x-x²-4x+5= -5²+2-x
c) x³-4x²+5x-1-3x³+4x²-7x+4= -2x³-7x²-2x+3
d) 2+3x-x²-2x³+5x³-4x²-3x+5= 7+6x-5x²-3x³
e) 9x²-3x+1-6x²-5x-3-6+2x-x²= 2x²-6x-10
f) 4-2x-3x²-5x²+2x-3-5+x+4x²= -6+x-4x²
g) -2x³-8x-4+2x²-6+2x-x³-3x-4x²+6x-1= -3x³-3x-11-2x²
h) 8-7x-x³+4x²-6x-5x²-2+10x-4x³-2x= 6-5x-5x³-5x²
2010-02-04T20:25:47+01:00
A)4x'-3x-2
b)-5x'-2+3x
c)-2x''-2x+3
d)7-5x'+3x''
e)2x'-6x-8
f)-4+x-4x'
g)-3x''-3x-11-2x'
h)6-5x-5x''-x'

'--potęga 2
''--potęga 3